Gender-based and grade-level mapping of student genetic literacy in the midst of the covid-19 pandemic - Alvin Dewa Yanuar; Sri Wahyuni; Diani Fatmawati; H Husamah; Lud Waluyo; Ahmad Fauzi (Biosfer: Jurnal Pendidikan Biologi, 2022)
The Covid-19 pandemic has resulted in the face-to-face teaching and learning process being shifted to distance learning which has the potential to affect student literacy levels. This quantitative study aims to determine the effect of gender and grade level on the genetic literacy of high school students in Malang. This survey research used a statement instrument as many as 17 items involving 97 students. Data collection was carried out from November to December 2021. The sampling technique used was cluster random sampling. The research data was tested using a Two-Way ANOVA analysis. The results showed that gender did not have a significant effect on genetic literacy, while class level has significant effect. Furthermore, gender and class level did not have a significant interaction. Further research that examines the effect of other variables on genetic literacy needs to be done.